Changes in Iridocorneal Angle and Anterior Chamber Structure in Eyes With Anatomically Narrow Angles: Laser Iridotomy Versus Pilocarpine. Issue 12 (December 2018) - Mogil, Rachel S.; Khezri, Nicole; Ren, Ruojin; Adleyba, Olga; Abumasmah, Ramiz; Ghassibi, Mark P.; Chien, Jason L.; Pearlstein, Adam; Patthanathamrongkasem, Thipnapa; Liebmann, Jeffrey M.; Ritch, Robert; Park, Sung chul
Abstract : Purpose: To compare the effects of laser iridotomy (LI) and pilocarpine on iridocorneal angle and anterior chamber structure in anatomically narrow angles (ANAs). Materials and Methods: Temporal LI was performed 90 minutes after 2% pilocarpine administration in patients with occludable ANA. Swept-source optical coherence tomography B-scans of the anterior segment were obtained at baseline, 60 minutes after 2% pilocarpine administration, and 1 week after LI. Angle-opening distance (AOD), trabecular-iris surface area (TISA), and angle recess area (ARA) were measured at the temporal, superior, nasal, and inferior quadrants. Anterior chamber depth (ACD) and lens vault (LV) were also measured. AOD, TISA, ARA, ACD, and LV were compared among 3 time points: at baseline, 60 minutes after 2% pilocarpine administration, and 1 week after LI. Results: Twenty-four eyes (24 patients; mean age, 55 y) were included. In all 4 quadrants and globally, AOD, TISA, and ARA increased from baseline after pilocarpine and after LI (all P <0.010). The increase in AOD, TISA, and ARA was greater after LI than after pilocarpine globally and in the temporal and superior quadrants (all P <0.040). ACD decreased and LV increased from baseline after pilocarpine (both P <0.001). Postpilocarpine anterior chambers were shallower with higher LV than post-LI (both P <0.016). Conclusion: LI is more effective than pilocarpine in widening the iridocorneal angle without significant shallowing the anterior chamber in eyes with ANA.